2016
DOI: 10.1261/rna.056101.116
|View full text |Cite
|
Sign up to set email alerts
|

Distinct splicing signatures affect converged pathways in myelodysplastic syndrome patients carrying mutations in different splicing regulators

Abstract: Myelodysplastic syndromes (MDS) are heterogeneous myeloid disorders with prevalent mutations in several splicing factors, but the splicing programs linked to specific mutations or MDS in general remain to be systematically defined. We applied RASL-seq, a sensitive and cost-effective platform, to interrogate 5502 annotated splicing events in 169 samples from MDS patients or healthy individuals. We found that splicing signatures associated with normal hematopoietic lineages are largely related to cell signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 66 publications
3
41
0
Order By: Relevance
“…Given distinct splicing responses, this has brought up the appealing hypothesis that these mutations may affect distinct molecular defects, but in some converging biological pathways, as we recently observed via analysis of splicing signatures in MDS patients (Qiu et al, 2016), which is in line with the synergistic effects of mutations in SRSF2 and SF3B1 in the mouse (Lee et al, 2016a). We now provide another potential converging mechanism, which is the induction of R-loops.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Given distinct splicing responses, this has brought up the appealing hypothesis that these mutations may affect distinct molecular defects, but in some converging biological pathways, as we recently observed via analysis of splicing signatures in MDS patients (Qiu et al, 2016), which is in line with the synergistic effects of mutations in SRSF2 and SF3B1 in the mouse (Lee et al, 2016a). We now provide another potential converging mechanism, which is the induction of R-loops.…”
Section: Discussionmentioning
confidence: 65%
“…Taking advantage of all mutations in the same cellular background, we first revisited an important problem with respect to diverse splicing responses induced by different splicing factor mutations (Ilagan et al, 2015; Qiu et al, 2016). We extracted total RNA from individual cell lines and used highly quantitative RNA annealing selection ligation followed by deep sequencing (RASL-seq), which we developed in the lab, to measure a large number (>5,000) of annotated alternative splicing events in humans (Li et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Recently, CD34 + bone marrow cells from MDS patients carrying different spliceosome mutations were interrogated in a single cohort using RNA-sequencing. Direct comparison of differential splicing Although only 5500 splicing events were interrogated, the study concluded that MDS-linked splicing signatures are primarily involved in cell cycle control and DNA damage responses.…”
Section: Mis-spliced Events In Srsf2 Del and P95h Mutated Mdsmentioning
confidence: 99%
“…Although only 5500 splicing events were interrogated, the study concluded that MDS-linked splicing signatures are primarily involved in cell cycle control and DNA damage responses. 29 Recently, CD34 + bone marrow cells from MDS patients carrying different spliceosome mutations were interrogated in a single cohort using RNA-sequencing.…”
Section: Gene Expression Profiling Reveals Dysregulated Heme Metabomentioning
confidence: 99%